Counterproductive behaviour at work: An investigation into reduction strategies - Kirk Chang (2018)
The present study examined the interrelation of personality characteristics, organizational justice, organizational citizenship behaviour (OCB), and counterproductive work behaviour (CWB). An anonymous questionnaire survey was conducted, with 1662 participants representing a wide variety of jobs across heterogeneous organizations in Thailand. Statistical analysis indicated that CWB can be predicted by the following personality characteristics; conscientiousness, agreeableness, self-esteem, extraversion, neuroticism and openness to experience. Moderation analysis discovered that the association between personality characteristics and CWB is moderated by three factors; distributive justice, interactional justice and OCB. Structural Equation Modelling was adopted in order to examine the efficacy of the identified moderators, and revealed that interactional justice has the strongest moderating effect, followed by distributive justice and finally OCB. Implications of the findings to organizational management and personnel practitioners are discussed accordingly, including; that the occurrence of CWB could be reduced through the implementation of organizational justice enhancement policies; and that the prevalence of OCB atmosphere at work could also help alleviate the impact of personality characteristics on CWB. © 2010 Taylor & Francis.